PENINGKATAN HASIL BELAJAR SISWA KELAS III SDN KESAUD KOTA SERANG PADA MATA PELAJARAN MATEMATIKA MELALUI METODE DEMONSTRASI - Andini Andini; Amat Hidayat; Ahmad Mubarok (Jurnal Anak Bangsa, 2022)
This study aims to determine the learning outcomes of third grade students at SDN Kesuad Serang City in mathematics through the demonstration method. This research uses a qualitative method with a classroom action approach (CAR) carried out collaboratively and in two cycles. The results showed that the average value of learning outcomes in the first and second cycles of the first and second meetings obtained an average value of 58.5 with a percentage increase of 68.5% and the second cycle obtained an average value of 72.7, with a percentage value achievement of 83.5%, then there is an increase in student learning outcomes. Likewise, the results of student observations showed an increase in student participation and activity in cycle I and cycle II by 90%. It can be concluded that the application of the demonstration method can improve student learning outcomes in Mathematics